Brain trauma induced hyperfibrinolysis: a tale of two cases diagnosed on wheels of rotational thromboelastometry - Goel, Deepak; Kotwal, Jyoti; Langer, Sabina; Saraf, Amrita; Prakhar, Pallavi (International Journal of Research in Medical Sciences, 2025)
Brain trauma including brain surgeries are medical emergencies which frequently cause abnormalities in the coagulation system which in turn leads to bleeding and poor outcomes. Routine coagulation tests often fail to diagnose these defects in the coagulation/fibrinolytic system in such critical emergencies. Viscoelastic tests are a rapid alternative which not only helps to diagnose these patients accurately but also at a much earlier time than routine coagulation tests. Here, we report two cases of brain surgeries who presented with bleeding in post operative period due to hyperfibrinolysis and they were correctly diagnosed and successfully treated with the help of rotational thomboelastometry whereas routine coagulation tests failed to do so.